Study Literatur Mewujudkan Budaya Positif dalam Menigkatkan Kinerja Guru SMPN 18 Gresik - Lilis Yuhana; Erny Roesminignsih; Syunu Trihantoyo; Amrozi Khamidi; Mochamad Nursalim; Kaniati Amalia (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze positive culture in improving teacher performance at SMPN 18 Gresik. Positive culture is an important element in creating a work environment that supports collaboration, innovation, and the welfare of educators. This study uses a literature study method with a qualitative approach to explore the concept, implementation strategies, and their impact on teacher professionalism. Data were collected from various relevant national and international journals in the period 2020–2024. The results of the study indicate that positive culture contributes to increasing teacher motivation, discipline, and effectiveness in teaching. The main factors in building a positive culture include the transformational leadership of the principal, collaboration between teachers, a fair reward system, and active participation of students and educators in creating a conducive learning environment. In conclusion, this study shows that the implementation of a positive culture can improve teacher performance, improve social relations in schools, and support the creation of a harmonious and productive educational ecosystem.  Keywords: Positive Culture, Teacher Performance, Transformational Leadership, Collaboration, Innovation